Assessing the costs and benefits of perioperative iron deficiency anemia management with ferric carboxymaltose in Germany - Froessler B; Rueger AM; Connolly MP (Dove Medical Press, 2018)
Bernd Froessler,1,2 Alexandra M Rueger,3,4 Mark P Connolly5,6 1Department of Anesthesia, Lyell McEwin Hospital, Elizabeth Vale, SA, Australia; 2Discipline of Acute Care Medicine, University of Adelaide, Adelaide, SA, Australia; 3Vifor Pharma, Munich, Germany; 4Charité Universitätsmedizin Berlin, Medizinische Klinik mit Schwerpunkt Kardiologie Campus Virchow-Klinikum, Berlin, Germany; 5Unit of PharmacoEpidemiology and PharmacoEconomics, Department of Pharmacy, University of Groningen, Groningen, the Netherlands; 6Global Market Access Solutions Sàrl, St-Prex, Switzerland Background: Perioperative administration of ferric carboxymaltose (FCM) was previously shown to reduce both the need for transfusions and the hospital length of stay in patients with preoperative iron deficiency anemia (IDA). In this study, we estimated the economic consequences of perioperative administration using FCM vs usual care in patients with IDA from the perspective of a German hospital using decision-analytic modeling.Materials and methods: The model was populated with clinical inputs (transfusion rates, blood units transfused, hospital length of stay) from a previously reported randomized trial comparing FCM vs usual care for managing IDA patients undergoing elective abdominal surgery. We applied a hospital perspective to all costs, excluding surgery-related costs in both treatment arms. One-way sensitivity analyses were undertaken to evaluate key drivers of cost analysis.Results: The average costs per case treated using FCM compared to usual care were €2,461 and €3,246, respectively, for resource expenses paid by hospital per case. This would suggest potential savings achieved with preoperative intravenous iron treatment per patient of €786 per case. A sensitivity analysis varying the key input parameters indicated the cost analysis is most sensitive to changes in the length of stay and the cost of hospitalization per day.Conclusion: Perioperative administration of FCM results in cost savings to hospitals based on reduced blood transfusions and length of stay following elective abdominal surgery. Keywords: intravenous iron, economic evaluation, anemia, iron deficiency, blood transfusion, patient blood management